ANALISIS KINERJA KEUANGAN DAERAH PROVINSI SULAWESI TENGAH TAHUN 2016-2023 - Nur, Putri Alya; Tope, Patta; Sading, Yunus (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to analyze the regional financial performance in terms of revenue variance, fiscal decentralization, financial independence, effectiveness, and efficiency of regional finance, as well as to examine the influence of financial performance on the economic growth rate in Central Sulawesi Province for the period 2016–2023. A quantitative approach was employed, using two methods of analysis: descriptive analysis based on financial ratios to evaluate regional financial performance, and log-log regression analysis to measure the elasticity of the influence of financial performance variables on economic growth. The results show that during the 2016–2023 period: (1) Regional financial performance, based on revenue variance analysis, generally met the established criteria, with revenue realization tending to exceed the budget. The fiscal decentralization ratio fell into the medium category, while the level of financial independence was relatively low, indicating a high dependency on the central government in an instructive relationship pattern. The effectiveness ratio of locally generated revenue (PAD) demonstrated a highly effective performance; however, the efficiency ratio of financial management was still relatively low. (2) The regression analysis results indicated that the financial independence ratio, PAD effectiveness, and financial efficiency did not have a significant influence on regional economic growth. These findings suggest that although the effectiveness of regional financial management is good, the low level of independence and suboptimal efficiency remain obstacles to promoting economic growth. Additionally, economic growth in Central Sulawesi Province is more heavily influenced by private sector activities and the dominance of the mining sector.